Education for Sustainability: Implications for Curriculum and Pedagogy - Kuzich, Sonja (National and Kapodistrian University of Athens, 2011)
The need to ameliorate the effects of unsustainable human actions and to implement an effective plan for the future of society has led UNESCO to focus on education as a crucial vehicle for this endeavour. The consensus amongst sustain ability 'thinkers' and practitioners is that education needs to be re-oriented toward a holistic, interdisciplinary, systems approach in order to precipitate the profound change in mindset required. Such change involves an understanding and action competence around the interdependence of all four pillars of sustainability: environmental, political, economic and social/cultural. This has tremendous implications for the educational system. There is a gap between the kind of thinking and action that is required to move towards a more sustainable future and the way schools currently operate. To develop future learners who have the knowledge, skills and capacity to address the root causes of unsustainability requires a wholesale transformation of the foci of curriculum and teacher pedagogy. This paper discusses the implications education for sustainability will have on what, and how, our teachers teach and students learn.